Does one need to polish electrodes in an eight pattern? Automation provides the answer - Yoshikawa, Naruki; Akkoc, Gun Deniz; Pablo-García, Sergio; Cao, Yang; Hao, Han; Aspuru-Guzik, Alán (Digital Discovery, 2025)
Automation of electrochemical measurements can accelerate the discovery of new electroactive materials. One of the hurdles to automated electrochemical measurement is the pretreatment of electrodes because mechanical polishing is usually conducted manually. Here we investigate the automation of electrochemical measurements using a robotic arm. We demonstrate automated mechanical polishing using a station with a moving polishing pad and evaluate the effect of different polishing patterns. Our automatic method improved the corroded electrodes, and we found the effect of pattern was not significant, which diverges from the current common belief amongst practitioners that a figure eight pattern is best for pretreatment. This research is a step toward automating electrochemistry experiments without human intervention.
CRIS-Team Scopus Importer:2025-01-31